The relationship network of nuncios and forms of reward for its members at the imperial court of Rudolf II (1576–1612) (Theatrum historiae, 2019)
Unlike the Spanish envoys, the papal nuncios made use of individuals who were attached to the imperial court of Rudolf II. These were in particular members of the Privy Council or of the Aulic Council as well as the most influential representatives of the Czech nobility. The networks of the papal nuncios started playing a key role – with regard to the fact that the sovereign gradually stopped paying attention and carrying out the affairs of state – as centres of influence for pursuing papal interests and sources for gathering information. For their services, the members of these networks could require a wide range of specific rewards the papal court could provide them with.
Keywords: nunciature; imperial court; papacy; networks; Rudolf II